2022
DOI: 10.1007/s00018-022-04511-y
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of APPL1/Myoferlin facilitates adipogenic differentiation of mesenchymal stem cells by blocking autophagy flux in osteoporosis

Abstract: An imbalance of human mesenchymal stem cells (hMSCs) adipogenic and osteogenic differentiation is crucial in the pathogenesis of osteoporosis, and elucidation of the underlying mechanism is urgently needed. APPL1, an adaptor protein of the adiponectin receptor, was recently shown to be closely related to bone mass. However, the role of APPL1 in the imbalance of hMSC differentiation in osteoporosis is unclear. Therefore, we aimed to explore the mechanisms by which APPL1 alters hMSCs adipogenic differentiation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
4
3
0
Order By: Relevance
“…The Co-IP results showed that APPL1 had no binding relationship with MGP on protein ( Fig. 7 A ), which is consistent with the results of liquid chromatography combined with tandem MS (LC‒MS/MS) in our previous study ( 10 ). We confirmed that APPL1 knockdown increased both the mRNA and protein levels of the MGP gene, and APPL1 overexpression decreased the mRNA and protein levels of MGP in MSCs ( Figs.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The Co-IP results showed that APPL1 had no binding relationship with MGP on protein ( Fig. 7 A ), which is consistent with the results of liquid chromatography combined with tandem MS (LC‒MS/MS) in our previous study ( 10 ). We confirmed that APPL1 knockdown increased both the mRNA and protein levels of the MGP gene, and APPL1 overexpression decreased the mRNA and protein levels of MGP in MSCs ( Figs.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, APPL1 overexpression effectively alleviated osteoporosis and promoted osteogenic differentiation of MSCs, whereas APPL1 knockdown attenuated osteogenic differentiation of MSCs. Combined with our previous study ( 10 ), it suggests that APPL1 may be an important molecule leading to the abnormal balance of adipogenic and osteogenic differentiation of MSCs in osteoporosis.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations